Broadband terahertz ZnO photonic crystals fabricated by 3D printing. Issue 5 (1st April 2019) - Tubío, Carmen R.; Nóvoa, José Antonio; Martín, Jorge; Guitián, Francisco; Salgueiro, José Ramón; Gil, Alvaro
Abstract: ZnO has been demonstrated to be a promising material for optoelectronic applications in the terahertz (THz) spectral range. However, there have been no reports regarding the fabrication of ZnO structures to control THz radiation, as photonic crystal (PCs) materials. Here, we focus on the development of a functional ZnO PCs for the THz band. The functionality is provided by the design that is based on a woodpile lattice with the appropriate periodicity for the THz region. Using a three-dimensional (3D) printing technique, we fabricate 3D ZnO based PCs with an effective lattice constant to generate a bandgap at the THz region. The functionality of the resulting PC was evaluated using THz time-domain spectroscopy combined with theoretical simulations. The results demonstrate the 3D woodpile lattice structure has good optical properties in the THz frequency region. These results serve as a step for the development of new THz functional devices for optoelectronics applications.